Synergistic effects of cryoablation and GM-CSF in colorectal liver metastases management in tumor-bearing mice - Junfeng Wang; Dalu Kong (Iranian Journal of Basic Medical Sciences)
Objective(s): The use of cryoablation for colorectal liver metastases (CLM) remains limited and controversial. This study aimed to investigate the antitumor immune response following cryoablation combined with granulocyte-macrophage colony-stimulating factor (GM-CSF) treatment in a CLM mouse model.Materials and Methods: A CLM mouse model was established using BALB/c mice. The tumor-bearing mice were randomly divided into Control group, GM-CSF group, cryoablation group, and cryoablation + GM-CSF group. Tumor size, survival time, dendritic cells (DCs) count, serum cytokine levels (IL-4, IFN-γ), and the Th1/Th2 ratio (IFN-γ/IL-4) were compared among the four groups.Results: The combination of cryoablation and GM-CSF demonstrated synergistic effects, resulting in the smallest tumor lesion, longest mean survival time, and highest DC count on day 21 post-treatment compared to other groups. Both cryoablation alone and combined with GM-CSF significantly increased serum IFN-γ levels and suppressed IL-4 levels on day 21 compared to pre-treatment levels (P<0.05). Notably, the combination of cryoablation and GM-CSF significantly elevated the Th1/Th2 ratio (P<0.05).Conclusion: Combining cryoablation with GM-CSF treatment holds promise for CLM management. It exhibits increased DC infiltration within the tumor microenvironment, enhanced immune responses, and prolonged survival in tumor-bearing mice.